The Natural History and Clinical Syndromes of Degenerative Cervical Spondylosis - John C. Kelly; Patrick J. Groarke; Joseph S. Butler; Ashley R. Poynton; John M. O'Byrne (Advances in Orthopedics)
Cervical spondylosis is a broad term which describes the age related chronic disc degeneration, which can also affect the cervical vertebrae, the facet and other joints and their associated soft tissue supports. Evidence of spondylitic change is frequently found in many asymptomatic adults. Radiculopathy is a result of intervertebral foramina narrowing. Narrowing of the spinal canal can result in spinal cord compression, ultimately resulting in cervical spondylosis myelopathy. This review article examines the current literature in relation to the cervical spondylosis and describes the three clinical syndromes of axial neck pain, cervical radiculopathy and cervical myelopathy